Leucocyte protein Trojan, a possible regulator of apoptosis. Issue 2 (28th December 2016) - Petrov, Petar; Syrjänen, Riikka; Uchida, Tatsuya; Vainio, Olli
Abstract : Trojan is a leucocyte‐specific protein, cloned from chicken embryonic thymocyte cDNA library. The molecule is a type I transmembrane protein with an extracellular CCP domain, followed by two FN3 domains. Its cytoplasmic tail is predicted to possess a MAPK docking and a PKA phosphorylation sites. Trojan has been proposed to have an anti‐apoptotic role based on its differential expression on developing thymocyte subpopulations. Using a chicken cell line, our in vitro studies showed that upon apoptosis induction, Trojan expression rises dramatically on the surface of surviving cells and gradually decreases towards its normal levels as cells recover. When sorted based on their expression levels of Trojan, cells with high expression appeared less susceptible to apoptotic induction than those bearing no or low levels of Trojan on their surface. The mechanism by which the molecule exerts its function is yet to be discovered. We found that cells overexpressing Trojan from a cDNA plasmid show elevated steady‐state levels of intracellular calcium, suggesting the molecule is able to transmit cytoplasmic signals. The mechanistic nature of Trojan‐induced signalling is a target of future investigation. In this article, we conducted a series of experiments that suggest Trojan as an anti‐apoptotic regulator.